2020
DOI: 10.1038/s41379-020-00649-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic pathology in patients dying of COVID-19: a series of 40 cases including clinical, histologic, and virologic data

Abstract: The novel coronavirus SARS-CoV-2 (coronavirus disease 19, or COVID-19) primarily causes pulmonary injury, but has been implicated to cause hepatic injury, both by serum markers and histologic evaluation. The histologic pattern of injury has not been completely described. Studies quantifying viral load in the liver are lacking. Here we report the clinical and histologic findings related to the liver in 40 patients who died of complications of COVID-19. A subset of liver tissue blocks were subjected to polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
285
6
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(342 citation statements)
references
References 22 publications
23
285
6
11
Order By: Relevance
“…It has been suggested that hepatic steatosis might develop during the course of COVID-19 [31]. Histopathological examinations of the liver in COVID-19 patients have shown hepatic steatosis, mild lobular and portal inflammation [31,32]. The decrease in L/S in the progressive group on followup that was identified in our study might be attributed to hepatic steatosis.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been suggested that hepatic steatosis might develop during the course of COVID-19 [31]. Histopathological examinations of the liver in COVID-19 patients have shown hepatic steatosis, mild lobular and portal inflammation [31,32]. The decrease in L/S in the progressive group on followup that was identified in our study might be attributed to hepatic steatosis.…”
Section: Discussionsupporting
confidence: 62%
“…It has been suggested that hepatic steatosis might develop during the course of COVID-19 [31]. Histopathological examinations of the liver in COVID-19 patients have shown hepatic steatosis, mild lobular and portal inflammation [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…In stark contrast to the early changes in circulating lipids, a subset of lipids (predominantly TAG, DAG, and PE) began to rise in the circulation between 24 and 72h in patients that subsequently exhibited a slow recovery or die. In addition to lipolysis and hypermetabolism, patients with critical illness experience pathologic alterations in liver such as hepatic steatosis [31][32][33][34][35] . Studies in severe burn trauma associate the browning of white adipose tissue with enhanced lipogenesis in liver 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Cholestatic features such as bile duct proliferation, portal inflammatory infiltrates, and in some cases, canalicular/ductular bile plugs have been reported in post-mortem evaluations on COVID-19 patients. 49,119 The cytokine storm characteristic of the SARS-CoV-2associated viral sepsis 120 may be a major contributing factor, since cytokines like TNF-alpha, IL-1 and IL-6 can induce hepatocellular cholestasis by down-regulating hepatobiliary uptake and excretory systems, 121,122 resembling the pathomechanisms seen in sepsis-induced cholestasis. [121][122][123][124][125] Further studies will have to explore In addition to hepatocellular features, bile duct changes, such as ductular proliferation have been observed in postmortem studies.…”
Section: S Ir S -Induced Chole S Ta S Is and B Ile Duc T Alter Ati mentioning
confidence: 99%